2018
DOI: 10.1177/2051415818762683
|View full text |Cite
|
Sign up to set email alerts
|

Improving the safety and tolerability of local anaesthetic outpatient transperineal prostate biopsies: A pilot study of the CAMbridge PROstate Biopsy (CAMPROBE) method

Abstract: Objectives:The aim of this study was to pilot the use of a bespoke device (CAMPROBE, the CAMbridge PROstate Biopsy) to enable routine outpatient free-hand local anaesthetic (LA) transperineal prostate biopsies.Materials and methods:The CAMPROBE prototype was designed and built in our institution. Men on active surveillance due prostate resampling were invited to have a CAMPROBE biopsy as an alternative to repeat transrectal ultrasound-guided prostate biopsies (TRUSBx) as part of an approved trial (NCT02375035)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
(35 reference statements)
1
24
0
2
Order By: Relevance
“…This may be attributable to the anxiety of having the procedure in a day surgery theatre setting, where there are more stages of preoperative checking and monitoring compared to an outpatient clinic, increasing the perceived invasiveness of the procedure in the day surgery environment. The CAMbridge PROstate Biopsy (CAMPROBE) study reported good tolerability with 1% lignocaine used as the LA; however, only a median of 11 biopsies were taken compared to an average of 24 cores in our present series . Smith et al.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This may be attributable to the anxiety of having the procedure in a day surgery theatre setting, where there are more stages of preoperative checking and monitoring compared to an outpatient clinic, increasing the perceived invasiveness of the procedure in the day surgery environment. The CAMbridge PROstate Biopsy (CAMPROBE) study reported good tolerability with 1% lignocaine used as the LA; however, only a median of 11 biopsies were taken compared to an average of 24 cores in our present series . Smith et al.…”
Section: Discussionmentioning
confidence: 64%
“…Other freehand biopsy approaches reported, either use a coaxial needle placed into the perineum or the biopsy gun needle itself is visualised within the perineum. These techniques, and the recent reports of the CAMPROBE device, an elegant modification of a co‐axial needle, that facilitates ‘freehand’ biopsy utilise a ‘fan technique’, which may still under sample the anterior apical prostate, especially in large glands . Freehand needle LA TP techniques are described as being technically challenging and have a steep learning curve .…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for sedation or GA relates to patient tolerability due to the exaggerated positioning of the patient required to place a stepper and grid, as well as the need for a skin puncture per biopsy taken. Advancements have recently been made in device technologies to allow for TPBx to be performed under LA using the PPTAS and other devices 11,13–15 . This method not only benefits the patient by eliminating the risk of undergoing GA but also has a potential economic impact on the healthcare system given the reduced resources required.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the Cambridge Prostate Biopsy (CAMPROBE), developed by Thurtle et al. [ 70 ], has shown to be effective in administering local anaesthesia with reduced pain and 87% preference over TRUS biopsy. Technically, this is similar to the transrectal biopsy; the MRI targeted transperineal biopsy can be either cognitive guided, MRI software fusion biopsy, or in-bore MRI transperineal biopsy.…”
Section: Mri-tbmentioning
confidence: 99%